2017
DOI: 10.1242/jcs.177170
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase A regulates the Ras, Rap1 and TORC2 pathways in response to the chemoattractant cAMP in Dictyostelium

Abstract: Efficient directed migration requires tight regulation of chemoattractant signal transduction pathways in both space and time, but the mechanisms involved in such regulation are not well understood. Here, we investigated the role of protein kinase A (PKA) in controlling signaling of the chemoattractant cAMP in Dictyostelium discoideum. We found that cells lacking PKA display severe chemotaxis defects, including impaired directional sensing. Although PKA is an important regulator of developmental gene expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 88 publications
1
21
0
Order By: Relevance
“…Phospho-ERK1 and -ERK2 were detected using phospho-p44/42 MAPK antibody diluted 1:5000. PKB and PKA substrates phosphorylation was detected using phospho-Akt substrate and phospho-(Ser/Thr) PKA antibodies, respectively, diluted 1:2000 as described previously [17].…”
Section: Biochemical Assays and Immunoblotsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phospho-ERK1 and -ERK2 were detected using phospho-p44/42 MAPK antibody diluted 1:5000. PKB and PKA substrates phosphorylation was detected using phospho-Akt substrate and phospho-(Ser/Thr) PKA antibodies, respectively, diluted 1:2000 as described previously [17].…”
Section: Biochemical Assays and Immunoblotsmentioning
confidence: 99%
“…and that Protein Kinase A (PKA), which is activated by intracellular cAMP, negatively regulates the activity of upstream RasG, Rap1, and mTORC2 pathways ( Fig. 1) [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be a confounding influence on studies of 491 chemotaxis, since macropinocytosis uses the same actin machinery as 492 pseudopods and thus impairs chemotaxis(Veltman, 2015). In particular, we 493 found that macropinocytosis continues at a high rate in mutants of the PKA 494 catalytic subunit, possibly accounting for the strong chemotactic defect of these 495 strains(Scavello et al, 2017). This could also be a confounding issue for some 496 other strains with early developmental defects(Khosla et al., 2005, Wu et al, 497 1995, Rodriguez et al, 2008, Lee et al, 2005).…”
mentioning
confidence: 83%
“…Sensitivity to chemoattractants appears to be negatively and positively controlled by PKA, HECT ubiquitin ligase-dependent ubiquitination and a novel negative regulator of Ras signalling (Scavello et al, 2017;Pergolizzi et al, 2017;Xu et al, 2017), whereas stochastic as well as chemotactically oriented pseudopod formation could be driven by a coupled excitable Ras/PI(3-4)P2/F actin system (van Haastert et al, 2017;Li et al, 2018).…”
Section: Past and Present Of A Model Organismmentioning
confidence: 99%